Policy framework for pastoralism in Africa: Securing, protecting and improving the lives, livelihoods and rights of pastoralist communities - African Union (African Union, 2013)
The Policy Framework for Pastoralism in Africa, as presented in this report, is the first continent-wide policy initiative aiming to secure, protect and improve the lives of African pastoralists. Pastoralists make crucial – but often undervalued – contributions to economies in Africa in terms of their production systems, culture, and animal and plant resources. Yet human development and food security indicators in many pastoral areas are among the lowest on the continent. The objectives of the framework are to protect the lives, livelihoods and rights of pastoral people, and to reinforce the contribution of pastoral livestock to national, regional and continent-wide economies.